Proceedings of the Sixth Workshop on Computational Linguistics and Clinical Psychology 2019
DOI: 10.18653/v1/w19-3012
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Analysis of the Semantic Verbal Fluency Task in Persons with Subjective and Mild Cognitive Impairment

Abstract: The Semantic Verbal Fluency (SVF) task is a classical neuropsychological assessment where persons are asked to produce words belonging to a semantic category (e.g., animals) in a given time. This paper introduces a novel method of temporal analysis for SVF tasks utilizing time intervals and applies it to a corpus of elderly Swedish subjects (mild cognitive impairment, subjective cognitive impairment and healthy controls). A general decline in word count and lexical frequency over the course of the task is reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
2
14
1
Order By: Relevance
“…This seems to complement the scoring, but would be quite cumbersome to implement in the clinic. For at least some of these findings, such as the importance of temporal analysis (disfluencies), they might be implemented in other tasks such as measuring latencies in BNT, or temporally resolved measures on the SVF (Linz et al, 2019 ). Another adjustment in the present study was the addition of follow-up questions which were posed if certain elements of the trip were not mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems to complement the scoring, but would be quite cumbersome to implement in the clinic. For at least some of these findings, such as the importance of temporal analysis (disfluencies), they might be implemented in other tasks such as measuring latencies in BNT, or temporally resolved measures on the SVF (Linz et al, 2019 ). Another adjustment in the present study was the addition of follow-up questions which were posed if certain elements of the trip were not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…SVF are often used for investigating semantic processing and production. Persons with MCI perform worse than healthy controls on SVF tasks, and research suggests that semantic retrieval is impaired (Demetriou and Holtzer, 2017 ; Linz et al, 2019 ). A decline in verbal fluency can in fact be seen very early as shown in a series of studies investigating late middle-aged individuals at risk for MCI, where those having “early” MCI had deficits in verbal fluency (Mueller et al, 2015 , 2016 ; Johnson et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results generally highlight the importance and validity of neuropsychological measures in dementia research. To summarize key publications, we reported that: SCI/MCI is a highly heterogeneous diagnostic entity with significant impairments in all cognitive domains (Nordlund et al, 2005); SCI/MCI subjects with vascular disease performed worse on tests measuring speed/attention, visuospatial function, and executive function (Nordlund et al, 2007); SCI/MCI with AD markers performed overall worse, especially on tests of speed/attention and episodic memory (Nordlund et al, 2008); a combination of vascular disease and AD biomarkers was associated with executive impairment (Nordlund et al, 2011); memory, visuospatial, and language symptoms characterized incipient AD (Nordlund et al, 2010); executive and speed/attention symptoms characterized incipient SVD (Nordlund et al, 2010); and neuropsychological tests were the best predictors of dementia with a combination of markers further improving the predictive ability (Eckerström et al, 2013).…”
Section: Current σAtus and The φTure Of The Gothenburg MCImentioning
confidence: 99%
“…The collaboration with Dr. Dimitrios Kokkinakis and colleagues within the project 'Linguistic and extra-linguistic parameters for early detection of cognitive impairment' (Kokkinakis et al, 2016) is an important next step to further refine the study of cognitive functioning in relation to dementia progression, using novel technical and analytical tools other than traditional neuropsychological testing; see for instance Fraser et al (2017); Themistocleous et al (2018) and Linz et al, (2019).…”
Section: Current σAtus and The φTure Of The Gothenburg MCImentioning
confidence: 99%
“…The two leading theoretical views either suggest loss of semantic knowledge (i.e., structural view; Rohrer, Wixted, Salmon & Butters, 1995) or impaired executive control mechanisms (i.e., procedural view; Fernaeus & Almkvist, 1998). These control mechanisms include a strategic or non-strategic search through the semantic space (i.e., the semantic knowledge store, where mental representations of concepts reside (Hills, Todd and Jones 2015;Clark et al, 2016;Lerner, Ogrocki, & Thomas, 2009;Linz et al, 2017Linz et al, , 2019 as well as monitoring processes to suppress previously mentioned items or items that do not belong to the category.…”
Section: Introductionmentioning
confidence: 99%